Thermal characterization of P. moriformis oil and biodiesel. (15th May 2018) - Raslavičius, Laurencas; Striūgas, Nerijus; Felneris, Mantas; Skvorčinskienė, Raminta; Miknius, Linas
Graphical abstract: Highlights: This is the article on thermal analysis of P. moriformis oil and biodiesel. The impact of fuel composition on thermal degradation rate is studied. We investigated fundamental aspects of novel fuel structure and properties. P. moriformis biofuel is a promising extender option for diesel fuel. Abstract: Analysis of thermal properties of the new types of biofuels is very important, providing basis to estimate the limit values of the combustion process and the specific behavior of the fuel itself. This is especially important when new and often expensive types of fuel undergo the initial evaluation. In this paper, thermal and physical properties of P. moriformis oil and biodiesel, diesel fuel and their 30/70 and 70/30 blends have been analyzed by using thermogravimetric analysis methods – Differential Scanning Calorimetry (DSC) and Thermogravimetry (TGA/DTG). According to obtained thermograms, it is observed that boiling point temperatures and ignition temperatures of the samples taking place in following order: diesel < algal oil < algal biodiesel and diesel < algal biodiesel < algal oil, respectively. By using three different methods derived in literature, Calculated Cetane Index (CCI) was calculated for the tested fuels and the obtained values compared with the reference values. An outcome of an experiment based on a scientific method in which Cetane number is assigned as a function of density and thermogravimetric analysis index have shown a very strong correlation between CCI obtained for P. moriformis biodiesel and reference value for the same fuel found in scholarly publication. Finally, we concluded that there are wide possibilities to utilise P. moriformis biodiesel blended in various proportions with fossil fuel without significant modifications of diesel engines.